Dialogando com intelectuais negras nas relações raciais: memórias, narrativas e trajetórias - Amaral, Raisa Carolina Carvalho do (Universidade Federal de São Carlos, 2019)
Brazil being a slave country, where black women have been subjected to violence and unequal treatment that permeates society to this day. In this sense, in search of means of survival and fight against racial prejudice and discrimination, one sees in education an alternative for the valorization of African, AfroBrazilian and indigenous culture, drawn in the historical, social and anthropological dimensions of the reality of the country, such as as the need for a reeducation based on ancestral memories and inheritance. Understanding the need for thematic approaches to Race Relations and Gender in the school environment, cultural and community spaces with children and adolescents, based on social, political, economic, cultural, among others, education is important in the context of an egalitarian and in the critical formation of these subjects. With the urgency of approaching the references and the protagonism of black women, such as their powers and intellectualities, this work refers to the narrative of a black woman as a student of Biological Sciences dialoguing with other black intellectuals seeking to identify solutions and perspectives for women black society, education, and education, as well as their contributions to the anti-racist, sexist, and gender equity struggle.
Dialoguing with black intellectuals in racial relations: memories, narratives, and trajectories
Keywords: Mulheres Negras; Educação; Antirracismo; Gênero; Equidade; Black Women; Anti-racist Education; Gender; Equity; CIENCIAS HUMANAS::EDUCACAO